Pharmacognostical Identification of Arjuna, Punarnava and Jatamansi with Recapture of Concept of Substitution and Adulteration (AYUSHDHARA, 2023)
In recent era, growth in natural product market and interest in traditional system of medicine is seen and people are shifting towards the Ayurvedic theories of health management. But, growth in production is still linear and fast depletion of resources is creating the major trouble. To meet the deficit, practices of adulteration and substitution are used widely, which became burning problem in industry threatening the integrity of Ayurveda. Aim and Objective: The aim of this article is pharmacognostical identification of Arjun, Punarnava and Jatamansi with recapture of concept of adulteration and substitution, their cause, types, examples and other import aspects and identify areas that need further research. Methodology: The pharmacognostical identification of Arjun, Punarnava and Jatamansi was performed with their adulterant and substituent. The review of concept of adulteration and substitution was done from literature and more than 30 published research articles that were identified through a systematic search of major computerized medical databases. Observation and Result: The deforestation, extinction or evolution of many species, insufficient knowledge, unauthenticated practices about raw material collectively resulted in adulteration and substitution. The concept of substitution is known in Ayurveda as it is enlightened prominently in Vagbhata, Bhavprakash Yogratnakar and Bhaishajya ratnavali. The pharmacognostical identification of Arjun, Punarnava and Jatamansi was performed performed and shown with their adulterant and substituent. Discussion: Strategic planning and integrated approach towards mass production, supply chain management, IEC, proper advocacy, proper pharmacovigilance monitoring of raw materials and knowledge sharing is needed to trim down the gravity of adulteration. Scope of this article throws light on the concepts of substitution given by our preceptors and analyses these with the present-day prevailing trend of adulteration and substitution.